Case series of concurrent occurrence of sarcoidosis and breast cancer – A diagnostic dilemma. (2022) - Mehta, Asmita A.; Pavithran, Keechilat; Jose, Wesley M.; Vallonthaiel, Archana George; George, Richie; Sudhakar, Nidhi
Abstract: Sarcoidosis is a multi-system granulomatous disorder characterized by involvement of multiple systems with or without lymphadenitis. Pulmonary complications are common and may lead to morbidity. Breast cancer is one of the commonest malignancy among women across the world. There is an increased risk of malignancies in sarcoidosis. This association with cancer creates a diagnostic dilemma due to the predominant involvement of nodes and organ systems in both conditions. Here we report three cases of sarcoidosis with breast cancer diagnosed over one year.